STUDY ON ECONOMIC VALUES THROUGH THE ACTIVITIES OF THE MANAGER IN KAMPUNG PURUN, PALAM VILLAGE-BANJARBARU - Mutiani,; Lestari, Julia Armiyanti; Jumriani,; Permatasari, Nina; Syaharuddin,; Abbas, Ersis Warmansyah (International Journal of Psychosocial Rehabilitation, 2020)
Economic activity is simply done to meet the needs and the achievement of economic growth towards social welfare. Economic activity is not only inherent in sellers but can be in producers such as artisans. This article aims to describe the activity of artisans in the home industry that raises economic value. A qualitative approach is used in research by optimizing the role of researchers as human instruments. Analysis of Miles and Huberman's interactive model data was carried out to obtain saturated data. The results of the study describe the activities of the purun crafters including production and distribution activities. The availability of purun resources becomes the driving factor for the sustainability of weaving activities by the collecting group (arisan). The products produced are not only simple webbing but are also created and distributed either directly or indirectly. The economic value of purun crafters activities includes three aspects, namely; social, quantity, and environment. These three aspects are intended to illustrate that each economic activity has a certain pattern. Thus it can provide the development of the home industry, especially the purun village craftsmen strategically.